Active Control System Applied to Vibration Level Control in High-Speed Elevators - Marcos Gonçalves; Jose M. Balthazar; Clivaldo Oliveira; Maria E. K. Fuziki; Giane G. Lenzi; Angelo Marcelo Tusset (International Journal of Robotics and Control Systems, 2022)
This work presents an active control system applied to vibration level reduction in high-performance vertical transport, aiming at improving the passengers’ comfort in high-speed elevators. The control system design includes the use of a Proportional Integral Derivative (PID) control. Three strategies were proposed in order to achieve a 90% reduction in the vibration amplitudes: (I) the consecutive reduction of 90% of the displacements, (II) the consecutive reduction of 90% of the velocity, and (III) the consecutive reduction of 90% of the acceleration. The presentation of these three proposals allows their application for the use of different sensors. The performance of each strategy was evaluated through mathematical modeling and numerical simulations of a vertical transport with 4 degrees of freedom, submitted to excitations arising from rail deformations. Vibration and comfort levels in the cabin were numerically analyzed, taking into account ISO 2631 and BS 6841 standards for elevator lateral acceleration level and comfort level felt by passengers. Numerical simulations showed that the force required to reduce the vibration levels is practically the same for the three proposed strategies. However, strategy (III) – the successive reduction of 90% of acceleration – proved to be more efficient at improving passengers’ comfort level when compared to the other two strategies.